2017
DOI: 10.1016/j.corsci.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The intergranular oxidation susceptibility of thermally–treated Alloy 600

Abstract: The oxidation behaviour of thermally-treated Alloy 600 was studied using hydrogenated steam at 480°C, environment known to simulate pressurized water reactors conditions, and subsequently analyzed using analytical electron microscopy. Focused Ion Beam and analytical transmission electron microscopy provided definitive evidence of localized intergranular carbides decomposition and the formation of an intergranular Cr-rich oxide embryo. These results are discussed in this paper in terms of early stages of prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 41 publications
1
25
0
1
Order By: Relevance
“…A very similar corrosion phenomenon is well known to occur in nuclear materials exposed to pressurized water reactor (PWR) primary water environment: intergranular stress corrosion cracking (IGSCC). For the first time reported for 304 and 347 steel pipes in the 1960s [58], IGSCC was later observed also in Ni-based alloys [59] such as alloy 600 [60][61][62]. It is generally accepted that IGSCC is the caused by internal oxidation [63].…”
Section: Intergranular Oxidation Attackmentioning
confidence: 99%
“…A very similar corrosion phenomenon is well known to occur in nuclear materials exposed to pressurized water reactor (PWR) primary water environment: intergranular stress corrosion cracking (IGSCC). For the first time reported for 304 and 347 steel pipes in the 1960s [58], IGSCC was later observed also in Ni-based alloys [59] such as alloy 600 [60][61][62]. It is generally accepted that IGSCC is the caused by internal oxidation [63].…”
Section: Intergranular Oxidation Attackmentioning
confidence: 99%
“…На основе работ [4][5][6][7][8][9][10][11][12][13][14][15][16][17], выполненных методами рентгеновской дифракции, сканирующей микро скопии, рентгеновской фотоэлектронной спектро скопии, наблюдаются следующие общие призна ки. Продукты коррозии в аустенитных сталях со стоят из пористого внешнего и плотного внутрен него оксидного слоя.…”
Section: механизмы разрушения пассивностиunclassified
“…Alloy 600 is frequently reported to have high stress corrosion cracking (SCC) susceptibility in pressurized water reactor (PWR) primary water over the past decades [1][2][3][4][5][6][7]. Domian et al [8] were the first to develop a method for increasing the SCC resistance of Alloy 600 by thermal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, mill-annealed (MA) or solution-annealed (SA) alloys exhibited higher SCC susceptibility than thermally-treated (TT) alloys due to a lower IC coverage [8][9][10]. Subsequent research revealed that a semi-continuous network of ICs can also reduce SCC susceptibility effectively in hydrogenated steam environments [6,7,11,[12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%